Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1161/01.cir.0000128034.70732.c2
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Green Tea–Derived Catechin on Developing Versus Established Atherosclerosis in Apolipoprotein E–Null Mice

Abstract: Background-Oxidative stress has been implicated in vascular injury and atherogenesis, and antioxidant treatment has shown favorable results in preclinical studies. Despite this, antioxidant therapy has failed to show benefit in clinical trials. Failure of antioxidants in clinical trials may be partly because such therapy is started after atherosclerosis is already well established, whereas the benefits in animal models may be results from early initiation of antioxidants while atherosclerosis is still evolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 36 publications
6
143
0
2
Order By: Relevance
“…Catechins have been reported to be potent biomolecules responsible for the health benefits associated with regular drinking of tea [4] [5]. Studies have shown that catechins possess beneficial physiological activities such as antioxidants [6] [7], hypocholesterolemiant [8] [9], anti-atherosclerotic [10], anti-inflammatory [11], and anti-HIV activities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Catechins have been reported to be potent biomolecules responsible for the health benefits associated with regular drinking of tea [4] [5]. Studies have shown that catechins possess beneficial physiological activities such as antioxidants [6] [7], hypocholesterolemiant [8] [9], anti-atherosclerotic [10], anti-inflammatory [11], and anti-HIV activities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cat have been reported to have a variety of properties, including antibacterial 13 and anticarcinogenic activity, 14 in addition to their antidiabetic 15 and antiatherogenic effects. 16,17 Consequently, there is growing interest in the use of Cat for the treatment and prevention of human diseases. We have been studying the antiobesity effects of tea Cat in humans and rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Green tea is known to contain high levels of antioxidant components such as catechin (a polyphenolic antioxidant), and has been shown to provide various health benefits, based on extensive studies in humans and animals. [12][13][14] The DPPH antioxidant assay using PVA-based pellets offers a simple and practical method for measuring the antioxidant capacity of natural products.…”
Section: Resultsmentioning
confidence: 99%